Neonatal Morbidity and Mortality Following Combined Vaginal and Cesarean Deliveries in a Triplet Pregnancy at 31 Gestational Weeks - Hsing-Yu Chen; Chih-Ping Chen; Ming-Chao Huang (Elsevier, 2005)
Objective: To present details of neonatal morbidity and mortality following combined vaginal and cesarean deliveries in a triplet pregnancy at 31 gestational weeks. Case Report: A 33-year-old woman, gravida 3, para 1, was referred to our hospital for delivery after tocolytic failure in a triplet pregnancy at 31 gestational weeks. Vaginal delivery was allowed following verification of the vertex position of all three fetuses by transabdominal ultrasonography. The first two babies were delivered vaginally with an interval of 4 minutes. The third baby was delivered by cesarean section due to fetal distress and cervical contraction 38 minutes after the delivery of the second baby, and had Apgar scores of 1 and 7 at 1 and 5 minutes, respectively. All babies developed respiratory distress syndrome. The third baby suffered additionally from necrotizing enterocolitis, necrosis and perforation of the bowel, periventricular leukomalacia, and impairment of the liver and kidneys and died 2 weeks after delivery. The first two babies were discharged uneventfully about 1 month after delivery. Conclusion: This case shows that, in multiple pregnancies, an interdelivery interval longer than 30 minutes may be associated with an unfavorable outcome even after cesarean delivery. We suggest that prompt delivery should be considered when a high interdelivery interval occurs, and neonatal morbidity and mortality should be included in the parents' counseling in the management of vaginal delivery of triplet pregnancies.